2023
DOI: 10.1128/iai.00557-22
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia Promotes Its Own Uptake by Host Cells

Abstract: Wolbachia pipientis is an incredibly widespread bacterial symbiont of insects, present in an estimated 25 to 52% of species worldwide. Wolbachia is faithfully maternally transmitted both in a laboratory setting and in the wild. In an established infection, Wolbachia is primarily intracellular, residing within host-derived vacuoles that are associated with the endoplasmic reticulum.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Drosophila melanogaster JW18 cells, which carry a GFP-Jupiter construct [ 24 ], were treated with 10 μg/mL tetracycline to remove Wolbachia infection. The infection status was confirmed by PCR after four passages in the presence of antibiotic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila melanogaster JW18 cells, which carry a GFP-Jupiter construct [ 24 ], were treated with 10 μg/mL tetracycline to remove Wolbachia infection. The infection status was confirmed by PCR after four passages in the presence of antibiotic.…”
Section: Methodsmentioning
confidence: 99%
“…WalE1 is upregulated by Wolbachia during host pupation and purified WalE1 protein co-sediments with filamentous actin and increases actin bundling in vitro and in vivo . As the actin cytoskeleton is important for Wolbachia’s maternal transmission [ 23 ], and for its internalization by host cells [ 24 ], the WalE1 effector likely plays an important role in Wolbachia’s biology.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation analyses revealed different interactions between two Cardinium strains Our data showed that two cultures infected with Cardinium had different expressions, whereas no such effect was observed for Wolbachia. It was also observed that Wolbachia is a highly prevalent bacterial symbiont of insects, found in approximately 25 to 52% of insect species worldwide [93], and is more diverse than Cardinium. The NCBI currently contains approximately 150 annotated genomes from different species.…”
Section: Do Correlation Analyses Reveal Competition Between Cardinium...mentioning
confidence: 99%
“…After that, Wolbachia utilize the host actin cytoskeleton during oogenesis for efficient transmission and maintenance between Drosophila generations ( Newton et al, 2015 ). Actin-inhibiting drugs significantly abrogate Wolbachia uptake in the host, indicating that the host actin cytoskeleton plays an important role in Wolbachia transmission ( Ferree et al, 2005 ; Newton et al, 2015 ; Nevalainen et al, 2023 ).…”
Section: Wolbachia Phenotypesmentioning
confidence: 99%